Coastal tourism buisness resilience in coping with crisis in Sabah, Malaysia - Jennifer, Kim Lian Chan; Arif @ Kamisan Pusiran Etok (2018)
This paper examines the level of tourism business resilience and factors influencing the resilience as well as suggestions in enhancing tourism business resilience by the small and medium coastal tourism operators located in Sabah coastal region, Malaysia. A quantitative approach was employed by using questionnaires and supported by semi-sturctured interviews with 61 small and medium coastal tourism operators in Sabah. Findings show majority of tourism business operators generally have high perceived levels of resilience and acknowledge the importance of resilience in coping with crisis. Ownership of the businesses to ensure sustainability of the business, vast experience within the industry which leads to maintaining of its confidence and being well prepared, as well as location and its readiness to face any crisis, attributed to the business resilience. Suggestions to enhance the level of resilience include: sufficient financial resources for emergencies, development of effective contingency plans, diversification of businesses and products, relocation to new location, government and local community support, as well as the strengthening of safety measures. The findings provide in depth understanding of small and medium size, coastal tourism business resilience and subsequently its benefits to the government and tourism industry in terms of strengthening coastal business resilience in coping with crisis and disaster planning. It is also especially important in terms of providing relevant and sound approaches and strategies, that would enable the development of resilience training to guide coastal tourism businesses in other coastal locations.